Fast Rotating Neutron Stars: Oscillations and Instabilities - Krüger, Christian J.; Kokkotas, Kostas D.; Manoharan, Praveen; Völkel, Sebastian H. (Frontiers in Astronomy and Space Sciences, 2021)
We derive a set of time evolution equations for the investigation of non-axisymmetric oscillations of rapidly rotating compact objects in full general relativity, taking into account the contribution of a dynamic spacetime. Using our code, which features high accuracy at comparably low computational expense, we are able to extract the frequencies of non-axisymmetric modes of compact objects with rotation rates up to the Kepler limit. We propose various universal relations combining bulk properties of isolated neutron stars as well as of binary systems before and after merger; these relations are independent of the true equation of state and may serve as a valuable tool for gravitational wave asteroseismology. We also present an introductory example using a Bayesian analysis.